Construction and validation of an instrument to evaluate the approach of the knowledge society in teachers - Ponce Lopez, Itzetl (2020)
The aim of this work was to design and validate an instrument to evaluate the approach of the knowledge society in teachers. The instrument integrated the resolution of essential problems in society, management and co-creation of knowledge, use of ICTs, ethical life project and collaborative work. Subsequent to its elaboration, the instrument was subject to expert review for the analysis of the validity of the facie and content, and the application to a pilot group for the feasibility analysis of a sample of 418 teachers, in order to analyze the validity of construct and reliability. From these phases it is indicated that the experts suggested improvements to the instrument and proposed its construction through an analytical rubric. In the expert judgment, the instrument was validated in general terms (V> 0.80); however, in writing several items had to be improved. In the application to the pilot group, an excellent degree of satisfaction was obtained with the instrument, as well as with the understanding of instructions and items. The construct validity analysis showed the representation of all the items, and the explanation of more than 62% of the variance by three factors (1. Resolution of essential problems in society and Management and co-creation of knowledge; 2. Use of ICTs and ethical life project; 3. Collaborative work), being similar to what was revealed by the cluster analysis. The reliability of the instrument was relevant for exploratory purposes (Cronbach's Alpha: 0.750). It is concluded that the rubric has validity of content and construct, and appropriate reliability.